Determinants of Medical Supply Chain Performance in Tanzania: The Roles of Supply Chain Integration and Inventory Control - Mwashiuya, Stephano; Mchopa, Alban; Shayo, France (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study examines persistent inefficiencies in Tanzania's public medical supply chain, such as stockouts, expired medicines, and delivery delays, that undermine healthcare service delivery and the attainment of Sustainable Development Goal 3. Methodology: A deductive approach and explanatory cross-sectional survey design were employed. The researcher collected data from 289 healthcare workers in Songwe Region's health centres and dispensaries. Partial least squares structural equation modelling (PLS-SEM) was used in assessing the relationships among SCI, INC, and MSCP, drawing on Resource-Based View (RBV) and Institutional Theory (INT) as guiding frameworks. Findings: Both SCI and INC had statistically significant positive effects on MSCP, with INC (β = .516, p < .001) exerting a more decisive influence than SCI (β = .317, p < .001). The model explained 48.3% of the variance in MSCP, indicating moderate predictive power. Unique Contribution to Theory, Policy, and Practice: This study contributes to theory by integrating RBV and INT to explain medical supply chain outcomes in low-resource settings. Practically, it highlights the need for policy enforcement, digital infrastructure investment, and targeted training to enhance supply chain performance. The findings provide actionable insights for health policymakers and development partners aiming to improve logistics systems in Tanzania and similar contexts.